Public speaking: An audience-Centered approach (Giáo trình Anh văn dành cho sinh viên khoa Anh văn trường Đại học Tổng Hợp Tp. HCM - Steven A Beebe
The book contains 5 parts. Part 1: Introduction to Public Speaking. Part 2: Overview of the Speechmaking Process. Part 3: Listening to Others. Part 4: Analyzing the Audience. Part 5: Developing Your Speech